MAKING A BOOK - Higgins, Nadia (Mankato, Minnesota : Amicus and Amicus Ink, 2019)
This book for elementary readers highlights the sequence of events from idea to a finished book. Full-color photographs and a timeline support each step of the project's process, from the author's first draft through budgeting, layout, and printing. A glossary, further resources, and an index are included"
Getting an idea on paper It takes a team Putting it all together t
Includes bibliographical references (page 31) and index.
Keywords: Books -- Juvenile literature; Publishers and publishing -- Juvenile literature; Authors and publishers